PENGARUH HARGA DAN MINAT BELI TERHADAP LOYALITAS PELANGGAN MIEREN KAHVE - Teuku Fahmi Aulia; Awaludin; Oki Prayogi (CV. Barokah Publsiher, 2025)
Customer loyalty is a key to the success of a company, not only in the short term but will also become a sustainable competitive advantage. Customers can be considered loyal if they are not easily influenced or switch to other companies or products. Customer loyalty can be created by various factors, namely price and purchase intention. A product will be accepted by consumers and survive in market competition if the product has provided satisfaction to consumers. This research aims to determine 1) the effect of price on customer loyalty at Mieren Kahve. 2) the effect of purchase intention on customer loyalty at Mieren Kahve. The type of research used is quantitative research with a sample of 96 respondents. The results obtained from this study are that price has a positive and significant relationship with customer loyalty and purchase intention has a positive and significant relationship with customer loyalty. The price variable is the variable that has a greater influence than the other variables. From this research, the researcher gives a suggestion that in the future Mieren Kahve is expected to maintain the consistency that has been built for many years.